Attitudes of Educators and Practitioners in the UAE Towards Elements of General Education in Learning Accounting - Roudaki, Jamal (Accounting Department,, 2004)
Most universities and higher education institutions in developing countries seem to concentrate on areas of specializations inteaching accounting. Many do not seem to give attention to general education despite the fact that local and international accreditation bodies (i.c. AACSB) require general education to be pan of the accounting degree. This paper aims at ï¬nding out how educators and practitioners differ in terms of their preference ratings of general education knowledge in accounting curriculum. A survey was conducted and discriminant analysis was applied to the collected data. The results suggest that. The two groups differ in their preference in general education. Practitioners seem to give more emphasis on general knowledge in the areas of art and science and business mathematics and statistics. while educators seem to pay more attention to general knowledge in marketing and economics.